Untangling Nucleotide Diversity and Evolution of the H Genome in Polyploid Hordeum and Elymus Species Based on the Single Copy of Nuclear Gene DMC1 - Sun, Dongfa; Sun, Genlou (PLOS ONE, 2012)
Numerous hybrid and polypoid species are found within the Triticeae. It has been suggested that the H subgenome of allopolyploid Elymus (wheatgrass) species originated from diploid Hordeum (barley) species, but the role of hybridization between polyploid Elymus and Hordeum has not been studied. It is not clear whether gene flow across polyploid Hordeum and Elymus species has occurred following polyploid speciation. Answering these questions will provide new insights into the formation of these polyploid species, and the potential role of gene flow among polyploid species during polyploid evolution. In order to address these questions, disrupted meiotic cDNA1 (DMC1) data from the allopolyploid StH Elymus are analyzed together with diploid and polyploid Hordeum species. Phylogenetic analysis revealed that the H copies of DMC1 sequence in some Elymus are very close to the H copies of DMC1 sequence in some polyploid Hordeum species, indicating either that the H genome in theses Elymus and polyploid Hordeum species originated from same diploid donor or that gene flow has occurred among them. Our analysis also suggested that the H genomes in Elymus species originated from limited gene pool, while H genomes in Hordeum polyploids have originated from broad gene pools. Nucleotide diversity (π) of the DMC1 sequences on H genome from polyploid species (π = 0.02083 in Elymus, π = 0.01680 in polyploid Hordeum) is higher than that in diploid Hordeum (π = 0.01488). The estimates of Tajima's D were significantly departure from the equilibrium neutral model at this locus in diploid Hordeum species (P<0.05), suggesting an excess of rare variants in diploid species which may not contribute to the origination of polyploids. Nucleotide diversity (π) of the DMC1 sequences in Elymus polyploid species (π = 0.02083) is higher than that in polyploid Hordeum (π = 0.01680), suggesting that the degree of relationships between two parents of a polyploid might be a factor affecting nucleotide diversity in allopolyploids.